2012
DOI: 10.3892/ijmm.2012.980
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the mitochondrial pathway in bruceine D-induced apoptosis in Capan-2 human pancreatic adenocarcinoma cells

Abstract: Abstract. The fruit of Brucea javanica L. is a common herb used in Chinese medicine for the treatment of a variety of cancers. Our research group has previously identified bruceine D (BD), a quassinoid found abundantly in B. javanica, to have potent cytotoxic effect on a number of pancreatic cancer cell lines, including Panc-1, SW1990 and Capan-1 cells. In the present study, we showed that BD was also able to inhibit the growth of the Capan-2 human pancreatic adenocarcinoma cell line, but it exerted only modes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 11 publications
3
8
0
Order By: Relevance
“…Therefore, treatment of A549 cells with bruceine D inhibited the cell cycle transition from the G1 to the S phase, suggesting that inhibition of cell cycle progression may be one of the mechanisms through which bruceine D inhibits the proliferation of A549 NSCLC cells. The present results are consistent with those of previous studies demonstrating that bruceine D induces G1 phase arrest in cancer cell lines (6,10).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Therefore, treatment of A549 cells with bruceine D inhibited the cell cycle transition from the G1 to the S phase, suggesting that inhibition of cell cycle progression may be one of the mechanisms through which bruceine D inhibits the proliferation of A549 NSCLC cells. The present results are consistent with those of previous studies demonstrating that bruceine D induces G1 phase arrest in cancer cell lines (6,10).…”
Section: Discussionsupporting
confidence: 94%
“…bruceine D, one of the major active quassinoids isolated from B. javanica , has been reported to exert an inhibitory effect against several types of cancer (8,22,23). In our previous research, bruceine D was found to exhibit a prominent suppressive effect on the proliferation of various pancreatic cancer cells, displaying only modest cytotoxicity against normal tissue cell lines, including GES-1 cells, human pancreatic progenitor cells and the WRL68 human hepatocyte cell line (6,8-10). Furthermore, bruceine D administration at a high dose (3 mg/kg) was associated with no obvious toxicity or distant organ metastasis in mice (8).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This can explain why the content of uracil showed a remarkable increase in control SW480 cells but a little shift in ABHD5 knockdown SW480 cells under the challenge of FU. To date, different pharmacological autophagy inhibitors have been developed and used in clinical cancer therapy 3539 . Different autophagy inhibitors block the autophagic process at different stages.…”
Section: Discussionmentioning
confidence: 99%
“…Brucea javanica oil emulsion can induce apoptosis of the bladder cancer cell line BIU-87 and human promyelocytic leukemia cell line HL-60 [ 21 , 22 ]. It was also found that BJOE can induce apoptosis of human pancreatic adenocarcinoma cells [ 23 ]. However, BJOE has been used with a high concentration and thus the toxic effects of BJOE on the normal cells are relatively high.…”
Section: Discussionmentioning
confidence: 99%